Treadmill training with an incline reduces ankle joint stiffness and improves active range of movement during gait in adults with cerebral palsy. Issue 10 (8th May 2017) - Lorentzen, Jakob; Kirk, Henrik; Fernandez-Lago, Helena; Frisk, Rasmus; Scharff Nielsen, Nanna; Jorsal, Martin; Nielsen, Jens Bo
Abstract: Purpose: We investigated if 30 min of daily treadmill training with an incline for 6 weeks would reduce ankle joint stiffness and improve active range of movement in adults with cerebral palsy (CP). Methods: The study was designed as a randomized controlled clinical trial including 32 adults with CP (GMFCS 1–3) aged 38.1 SD 12 years. The training group ( n  = 16) performed uphill treadmill training at home daily for 30 min for 6 weeks in addition to their usual activities. Passive and reflex mediated stiffness and range of motion (ROM) of the ankle joint, kinematic and functional measures of gait were obtained before and after the intervention/control period. Intervention subjects trained 31.4 SD 10.1 days for 29.0 SD 2.3 min (total) 15.2 h. Results: Passive ankle joint stiffness was reduced ( F  = 5.1; p  = 0.031), maximal gait speed increased ( F  = 42.8, p  < 0.001), amplitude of toe lift prior to heel strike increased ( F  = 5.3, p  < 0.03) and ankle angle at heel strike was decreased ( F  = 12.5; p  < 0.001) significant in the training group as compared to controls. Conclusion: Daily treadmill training with an incline for 6 weeks reduces ankle joint stiffness and increases active ROM during gait in adults with CP. Intensive gait training may thus be beneficial in preventing and reducing contractures and help to maintain functional gait ability in adults with CP. Implications for rehabilitation: Uphill gait training is an effective way to reduce ankle joint stiffness in adult with contractures. 6 weeks of daily uphill gait training improves functional gait parameters such as gait speed and dorsal flexion during gait in adults with cerebral palsy.